The Production and Evaluation of an Electrochemical Sensors for Strychnine and Its Main Metabolite Strychnine N-Oxide for Their Use in Biological Samples - Bakhtiyar Qader; Issam Hussain; Mark Baron; Rafael Estevez-Brito; John Paul Cassella; Jose Gonzalez-Rodriguez (Molecules, 2022)
Strychnine (STN) and its major metabolite Strychnine N-Oxide (SNO) were examined electrochemically. Both parent compounds and its major metabolite showed electroactivity on glassy carbon electrodes using CV and DPV techniques. One oxidation peak at 1008 mV was observed for STN with the optimum peak intensity at pH 7. SNO produced two oxidation peaks, at 617 mV and 797 mV, at pH 5. The peaks demonstrated irreversible behaviour and the irreversibility of the system was confirmed at different scan rates. A calibration curve was produced for both CV and DPV measurements and the sensitivity of the proposed EC method was good compared with previous electrochemical and non-electrochemical methods. The precision of oxidation peak of STN using the STN-MIP method produced a maximum value of 11.5% and 2.32% for inter-day and intraday %RSD, respectively. The average% recovery was around 92%. The electrochemical method has been successfully applied to the determination of STN in spiked plasma and urine samples. For SNO, both anodic peaks of SNO demonstrated irreversible behaviour. A different sweep rate was used for calculating the number of ‘transfer electrons’ in the system; based on this, the mechanism of oxidation reaction was proposed. Calibration curves for both oxidative peaks were produced using DPV measurements. The second anodic peak demonstrated high linearity and precision with %RSD < 1.96%.